USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES DURING CIVIL PROTECTION CLASSES - Babiichuk, Iryna Viktorivna; Romaniuk, Nataliia Mykolaivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2021)
Consideration of new optimal innovative forms and methods, as well as educational technologies in the organization of the educational process of functional training in civil protection, allowing students to acquire, update special knowledge, skills and abilities in civil protection within professional activities or knowledge.